Simulated medication errors: A means of evaluating healthcare professionals' knowledge and understanding of medication safety - Ramadaniati, Hesty Utami; Hughes, Jeff; Lee, Ya Ping; Emmerton, Lynne (2018)
OBJECTIVE: To determine multi-disciplinary perceptions of the clinical significance of medication errors (MEs), the responsible health professional(s), the contributing factors and potential preventive strategies. METHODS: The five simulated ME cases represented errors from five wards at a children's hospital in Australia. Pre-determined answers for each case were developed through consensus among the researchers. The root cause analysis (RCA) was undertaken via a questionnaire disseminated to physicians, nurses and pharmacists at the study hospital to seek their opinions on the ME cases. Agreement model between the participants and pre-determined responses regarding the contributing factors was conducted using general estimating equation (GEE) analysis. RESULTS: Of the 111 RCA questionnaires distributed, 25 were returned. The majority (93%) of respondents rated the significance of the MEs as either 'moderate' or 'life-threatening'. Furthermore, they correctly identified two contributing factors relevant to all cases: dismissal of policies/procedures or guidelines (90%) and human resources issues (87%). GEE analysis revealed varied agreement patterns across the contributing factors. Suggested prevention strategies focused on policy and procedures, staffing and supervision, and communication. CONCLUSION: Simulated case studies had potential use to seek front-line healthcare professionals' understanding of the clinical significance and contributing factors to MEs, along with preventive measures.